THE USE OF MODERN INNOVATIVE TECHNOLOGIES IN TEACHING ENGLISH (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This articleoutlines the great importance given to foreign languages in the Republic of Uzbekistan and the innovative technologies needed to study them